Educação do campo: políticas e práticas (SciELO - Editus - Editora da UESC, 2020)
In this volume, texts were selected, the main objective of which is to promote and deepen the debate of themes that intersect in the relations of rural and urban social movements with education, offering higher education teachers, managers, students, activists of social movements and basic education professionals a reading option on the subject.